1998
DOI: 10.1080/10826079808006882
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a Flavonoid Sample by Countercurrent Chromatography

Abstract: A quercitrin rich vegetal flavonoid sample was fractionated using a new hydrodynamic CCC apparatus based on the It0 scheme IV design. The Kromaton CCC apparatus has two spools with a tube coiling allowing work with two different apparatus volumes. The small "analytical" volume was 94 mL and the large "preparative" volume was 1.07 L. The fractionation of the flavonoid sample was done using the two machine volumes. The bi phasic liquid system was a non chlorinated solvent system, butanonelwater. W detection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A total of 170 papers (including review papers but excluding book chapters and patents) were found, of which we had access to 148 papers. These papers 12–159 comprise studies on two large groups of flavonoids: the free and the glycosylated flavonoids. From the first group, we found examples of the isolation of flavones, flavonols, isoflavonoids, flavanones, flavanonols, chalcones, anthocyanidines, proanthocyanidines, rotenoids, biflavonoids, triflavonoids, and theaflavins, which account for 45 references and two review papers (32% of the total).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 170 papers (including review papers but excluding book chapters and patents) were found, of which we had access to 148 papers. These papers 12–159 comprise studies on two large groups of flavonoids: the free and the glycosylated flavonoids. From the first group, we found examples of the isolation of flavones, flavonols, isoflavonoids, flavanones, flavanonols, chalcones, anthocyanidines, proanthocyanidines, rotenoids, biflavonoids, triflavonoids, and theaflavins, which account for 45 references and two review papers (32% of the total).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found to be a useful purgative. [7][8][9][10] In this paper, high-speed analytical countercurrent chromatography was used to select a suitable solvent system and HSCCC was applied to the purification of the three flavonoids, followed by the identification of these using LC-MS electrospray ionisation and NMR. In the seeds of O. indicum, there are a large amount of bioactive flavonoids such as baicalein, baicalin, chrysin, apigenin.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the CCC chromatogram of a 0.33 g injection. The compounds were identified using mass spectrometry as described in a recent article [14]. Table IV lists the chromatographic parameters that can be established from the CCC chromatogram.…”
Section: Separation Of a Flavonoid Samplementioning
confidence: 99%